ELASTISITAS DAN EFISIENSI BEBERAPA FAKTOR PRODUKSI PADA KILANG KAYU LAPIS DI SUMATERA DAN KALIMANTAN - Akub J Abdurachman; Kirsfianti L Ginoga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
The study of the elasticity and efficiency of several production factors of plywood mills was carried out at 14 plywood mills in Sumatra and Kalimantan. The result of analysis revealed that the value elasticity of four production variables i.e installed capacity (X1), number of administration labor (X2), number of technical labor (X3) and the number of raw material (X4) as follow O,7213; 0,0647; 0,0375 and 0,2906. It is shown that the elasticity of each production variable is still low. The ratio of marginal product value over marginal cost of variable X2, X3 and X4 are follow 0,856; 0,510 and 1,755, respectively. Therefore, the economic efficiency of production variables at 14 plywood mills in Sumatra and Kalimantan is not reached.